Why the long teeth? Morphometric analysis suggests different selective pressures on functional occlusal traits in Plio-Pleistocene African suids. Issue 4 (November 2022) - Yang, Deming; Pisano, Asli; Kolasa, Joan; Jashashvili, Tea; Kibii, Job; Gomez Cano, Ana R.; Viriot, Laurent; Grine, Frederick E.; Souron, Antoine
Abstract: Neogene and Pleistocene African suids displayed convergent evolutionary trends in the third molar (M3) morphology, with increasingly elongated and higher crowns through time. While these features can prevent premature loss of masticatory functionality and potentially increase long-term reproductive success, changes in dental occlusal traits such as enamel complexity and thickness can also improve chewing efficiency and increase short-term energetic return. While both long-term and short-term benefits can contribute to the thriving of a lineage, the selective pressures associated with each category can be different. To examine how crown elongation correlates with these functional occlusal traits, we selected M3s of Kolpochoerus, Notochoerus, and Metridiochoerus from Kenya and South Africa, dated between 3.0 Ma and 0.4 Ma. To account for dental wear, we used micro-computed tomography imaging of unworn/slightly worn M3s to simulate wear progression within each tooth. We compared morphometric representatives of occlusal enamel complexity and thickness among the specimens following their respective wear trajectories. We found that M3 elongation correlates with higher occlusal complexity and thinner enamel in Notochoerus and Metridiochoerus lineages through time. In Kolpochoerus, enamel complexity and thickness were generally maintained through time, despite M3 elongation. The differences in M3 morphometric trends suggest that Kolpochoerus likely experienced a different set of selective pressures on functional occlusal traits compared with Notochoerus and Metridiochoerus . The shared evolutionary trends of M3 specialization among Notochoerus and Metridiochoerus suggest similar selective pressures on their chewing efficiency and the possibility of a dietary niche overlap in more xeric habitats.